Factors influencing customers purchase intention towards organic food in Malaysia / Nurdiyana Madihah Badrul Hisham - Badrul Hisham, Nurdiyana Madihah (Faculty of Business and Management, 2019)
The purpose of this research is to study about the factors that influencing customers purchase intention towards organic food in Malaysia. This research identifies the factors that attributes to purchase intention such as health consciousness, environmental concern, perceived value and food safety. These factors will be used to identify or to determine which one of it has the most influential factors contributes to customer purchase intention towards organic food. The research is based on a sample of 110 respondents. The results show that health consciousness, environmental concern, perceived value and food safety have significant influence of purchase intention towards organic food. It involve the process of conducting the research such as in determining the sample, the reliability and validity of questionnaire and including the research design, sampling technique, data collection method also involving primary data, secondary source and data analysis technique. Among all of those factors, the most influencing factor that influence the customers purchase intention towards organic food is food safety with the significant at <0.05 level. Besides that, the research also comes with recommendation that will help the organic industry to improve the customers purchase intention towards organic food in the future.